The skill of time management for university students as a strategy to achieve academic success.A field study for students of the Institute of Science and Techniques of Physical Activity at the University of Laghouat and students of the Higher Training Tea - Mohammed gattaf; حمادي جمال; بعيط عيسى (sports creativity, 2025)
The study aims at identifying the degree of the study sample acquisition of time management skill as a strategy to achieve academic success. The sample includes 750 students who are studying at the Institute of Science and Techniques of Physical Activity at the University of Laghouat and the Higher training teacher’s School Talib Abdulrahman Laghouat. To check the hypotheses of the study, a questionnaire has been constructed to test students gaining of the skill of time management and it has been subjected to the scientific conditions (sincerity of the arbitrators, the validity of the content, and the calculation of the stability coefficients). After the distribution and retrieval of the research questionnaire, we have uploaded the raw data in the SPSS software and made the statistical treatment that are in line with the hypotheses of the study. The study concludes that the study sample has a high level of time management skill as a strategy to achieve academic success